Implicações dos sentidos atribuídos pelos psicólogos ao uso de álcool e outras drogas no tratamento de usuários em CAPS ad e Comunidades Terapêuticas - Pires, Ronaldo Rodrigues (2013)
The attention to problems arising from the use and addiction has been a challenge for public health in Brazil. One of the difficulties to competent and humane care of these users in the Unified Health System - SUS has been shown through studies that users of alcohol and other drugs, as being the target of stigma and prejudicial attitudes within the health services. The unpreparedness regarding training for this kind of attention is another barrier to be overcome. Sought to question the role of the psychologist as a worker overlaps in these health institutions, as this professional has been in increasing numbers among the components of multidisciplinary teams of health facilities. The relevance of this research is to contribute to a reflection on the inclusion of psychologists in public policy healthcare for users of alcohol and other drugs seeking to bring elements that contribute to the improvement of profession. The objective of this research was to understand the relationship between the meanings attributed by psychologists to alcohol and other drugs and its implications in the treatment of users of Psychosocial Care Centers - CAPS ad and the Therapeutic Communities. Was then carried out a search using qualitative interviews with three psychologists these institutions. The interviews were analyzed using the technique of content analysis and had the help of the software Atlas - Ti 5.2 in the preparation of the results. Based on interviews of psychologists surveyed, it was found that the substances are seen by them as being essentially negative properties that would have the ability to subjugate the subject to a state of illness and dependency. Furthermore, the meanings attributed to drug use as a negative imply ideological differences on the issue of Harm Reduction, while policy carefully since this is understood by psychologists as a strategy for reducing the use of substances. The major implication of these senses occurs in the field of practice in which one realizes that most of the activity is intended to provide strategies for reducing the use of substances, not being included interventions in complex contexts involving the process of drug addiction. Realized that even acknowledging stigma user, interventions to reduce this stigma need to be more effective. Most practices are performed by psychologists in individual and group consultations indicate that the bias predominantly clinical formation. It takes the aim of these practices become increasingly broad in order to intervene in complex contexts involving the health of drug addicts.